Performance evaluation of selected moderately stemphylium blight resistant lentil lines/varieties in yield (Asian Journal of Medical and Biological Research, 2019)
Blight is an important disease that cause devastating yield loss now a days. That’s why, an investigation was carried out at the Regional Agricultural Research Station (RARS), Bangladesh Agriculture Research Institute (BARI), Barishal for screening of lentil germplasms against stemphylium blight in terms of yield and yield attributes. To find the best genotype, 40 moderately stemphylium resistant lentil lines/ genotypes were used and their different yield contributing characters were analysed. In this study, it has been observed that the long delay of 1st flowering was recorded in BD-5982 and BD-5996 while early flowering in BD-3927 and BARI masur-7. The highest 50% flowering days was recorded in BD-3983, BD-4024, BD-4053 etc. and lowest in BD-3922. Long maturation period of 111.5 days was recorded in BD-4024 and that of short maturity date was recorded in BD-3924 and BD-3927. The highest plant height was observed in BD-3974 and lowest was in BD-4127. The maximum number of branches per plant was observed in BD-3936 and BD-4024 and minimum was found in BD-4097. Maximum number of pods per plant was recorded in BD-3922 and minimum number of pods per plant was in BD-4053. The lowest number of seeds per pod was recorded in BD-4053. The highest 100 seed weight was recorded in BD-5986 and the lowest was observed in BD-4127. Maximum biological yield was recorded in BD-4053 and minimum was in BD-5989. The highest and lowest grain yield was recorded in BD-5983 and BD-4024, respectively. This finding will help researcher to develop new variety in near future.Asian J. Med. Biol. Res. June 2019, 5(2): 100-106